If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.12x + 0.6(x + -4) = 0.01(3x + -1) Reorder the terms: 0.12x + 0.6(-4 + x) = 0.01(3x + -1) 0.12x + (-4 * 0.6 + x * 0.6) = 0.01(3x + -1) 0.12x + (-2.4 + 0.6x) = 0.01(3x + -1) Reorder the terms: -2.4 + 0.12x + 0.6x = 0.01(3x + -1) Combine like terms: 0.12x + 0.6x = 0.72x -2.4 + 0.72x = 0.01(3x + -1) Reorder the terms: -2.4 + 0.72x = 0.01(-1 + 3x) -2.4 + 0.72x = (-1 * 0.01 + 3x * 0.01) -2.4 + 0.72x = (-0.01 + 0.03x) Solving -2.4 + 0.72x = -0.01 + 0.03x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.03x' to each side of the equation. -2.4 + 0.72x + -0.03x = -0.01 + 0.03x + -0.03x Combine like terms: 0.72x + -0.03x = 0.69x -2.4 + 0.69x = -0.01 + 0.03x + -0.03x Combine like terms: 0.03x + -0.03x = 0.00 -2.4 + 0.69x = -0.01 + 0.00 -2.4 + 0.69x = -0.01 Add '2.4' to each side of the equation. -2.4 + 2.4 + 0.69x = -0.01 + 2.4 Combine like terms: -2.4 + 2.4 = 0.0 0.0 + 0.69x = -0.01 + 2.4 0.69x = -0.01 + 2.4 Combine like terms: -0.01 + 2.4 = 2.39 0.69x = 2.39 Divide each side by '0.69'. x = 3.463768116 Simplifying x = 3.463768116
| 15x+120=x | | 8y+6y=56 | | (29/36)x+120=x | | 60x-13=72x-3-24x | | 103-2x=16x+21 | | 5x-15+2x-14=x-11 | | 5x-2x+12=35-4x-9 | | y=-(1+1)(1-3) | | 2g-8=10-4g | | X^2+7-9=0 | | 105*13/35*8/9 | | 5x-3.2=2x+2.8 | | 7x-91=2x-6 | | 32=17+x/2 | | 9x+10=3x+40 | | 48-2x=16x+24 | | F-2=3f+6 | | 5(x+3)+3(x-1)=-9 | | X/4+7=14 | | 21=(5x/6)+(3x/2) | | 2(x-4)+3(x+5)=2x | | 5.3q-1.9-4.6q=-0.3q-1.5 | | 2x-8+3x+18=2x | | 33/25*10/117*27/22 | | -2y+5x=-9 | | 62-9x=7x+18 | | x/3-26 | | 2x-5=57 | | x/2=48 | | x/4+x/3=7/4 | | 2f-7=43 | | x/6=15 |